The Challanges In Implementing Thematic Learning Based On Scientific Approach At Elementary School In The Industrial Revolution 5.0 - Yorenza Meifinda; Silvio Juliana Nabela (FIP Unimed, 2023)
The objective of this research was to provide an appropriate perspective for Indonesia to adopt innovations, application technique and sustainable technology based on the conditions faced by Indonesia due to the development of the industrial revolution 5.0. The method used in this research was descriptive qualitative methods. The method was used to describe, illustrate, or portrait the facts systematically, factually and accurately, as well as the correlation between the phenomena investigated. The positive influence of industry 5.0 is the effectiveness and efficiency of resources and production costs despite the impact on reducing in the number of jobs. Industry 5.0 needs a workforce that has skills in digital literacy, technological literacy, and human literacy. What should be done by teachers in the era of the industrial revolution 5.0; first is applying 4C (Communication, Collaboration, Critical thinking, and Creativity). Second, teachers should master technology. Third, teachers should open toward globalization. Fourth, teachers should improve their competence. Fifth, besides teachers, everyone should open with globalization too and improve their technology knowledge and skill. Sixth, learning should be relevant to students. Thus, the industrial revolution 5.0 not only provides opportunities, but also challenges for millennial. Keywords: Thematic learning, scientific, industrial Revolution 5.0